Control of cooperative manipulators in holding deformable objects - Alkathiri, A A; Zainul Azlan, Norsinnira (IOP Publishing, 2017)
This paper presents the implementation of a control system to control cooperative manipulators to hold deformable objects. The aim is to hold the deformable object without having information on the shape and stiffness of the deformable object beforehand. The prototype of a pair of manipulators has been designed and built to test the controller. A force sensor and a rotary encoder are used to give feedback to the controller, which controls the DC motor actuators accordingly. A position proportional-integral-derivative (PID) controller technique has been applied for one of the manipulators and a PID force control technique is applied to the other. Simulations and experimental tests have been conducted on models and the controller has been implemented on the real plant. Both simulation and test results prove that the implemented control technique has successfully provided the desired position and force to hold the deformable object with maximum experimental errors of 0.34mm and 50mN respectively.